Comparative biofilm-forming ability between Clostridioides difficile strains isolated in Latin America and the epidemic NAP1/027 strain - Morais, Maria Luana Gaudencio dos Santos; Santos, Mayara Gilde Castro; Costa, Cecília Leite; Martins, Conceição Silva; Leitão, Renata Ferreira de Carvalho; de Melo Pacífico, Dvison; Quesada-Gómez, Carlos; Castelo Branco, Débora; Ferreira, Eliane de Oliveira; Brito, Gerly Anne de Castro (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction One of the challenges in treating Clostridioides difficile infection (CDI) is that the bacterium forms biofilms, a critical virulence mechanism known to promote antibiotic resistance and, as a result, consequently, a higher recurrence of the disease. The goal of this study was to compare the ability of three MLST Clade 2 strains to form a biofilm in vitro: ICC-45 (ribotype SLO231/UK[CE]821), a ST41 toxinotype IXb isolated in Brazil; and two epidemic NAP1/027/ST01 strains: NAP1/027/ST01 (LIBA5756), isolated during a 2010 outbreak in Costa Rica and the reference epidemic strain NAP1/027/ST01 (R20291); and ATCC700057, a non-toxigenic strain. Methods The ability of strains to form biofilm was evaluated using crystal violet staining. In addition, samples were stained with the Film Tracer biofilm matrix (Invitrogen®) and the biofilm matrix thickness was measured using confocal microscopy. The matrix architecture was determined using Scanning electron microscop. Confocal microscopy was used to detect the presence of toxin A (tcdA) using an anti-Clostridioides difficile TcdA antibody. The expression of virulence genes (tcdA, tcdB, tcdC, cdtB, spo0A, slpA, cwp66 and cwp84) was examined, as well as the effect of antibiotics metronidazole (MTZ) and vancomycin (VAN) on biofilm growth. Results All of the strains tested formed a moderate biofilm with 1.1 <DO570nm>3.5. After 72h, biofilm biomass of the NAP1/027/ST01 epidemic strains (LIBA5756 and R20291) was significantly higher than ICC-45 and ATCC 700057 biofilms, as confirmed by electron and confocal microscopy. At 120h, the LIBA5756 biofilm biomass decreased compared to other strains. The toxigenic strains R20291 or LIBA 5756 had higher expression of genes tcdA, tcdB, tcdC, cdtA, slpA and spo0A than ICC-45, but there were no significant differences in the expression levels of cdtB, cwp66 and cwp84. In epidemic strains, VAN and MTZ inhibited biofilm formation; however, in the ICC-45 strain, MIC concentrations of VAN and MIC and 4MIC of MTZ did not inhibit biofilm formation. Conclusion The three MLST Clade 2 isolated from different rybotipes, two of which were isolated from Latin America, are competent biofilm-forming bacteria, indicating their ability to induce C. difficile infection recurrence, making treatment difficult.